2007
DOI: 10.1063/1.2437687
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Si doping on the electrical properties of B12As2 thin films on (0001) 6H-SiC substrates

Abstract: The ability to control the resistivity of the wide band gap semiconductor B 12 As 2 by doping with silicon was verified. The electrical properties of nominally undoped and Si-doped rhombohedral B 12 As 2 thin films on semi-insulating 6H-SiC ͑0001͒ substrates prepared by chemical vapor deposition were subjected to Hall effect measurements. Varying the Si concentration in the B 12 As 2 thin films from 7 ϫ 10 18 to 7 ϫ 10 21 at./ cm 3 ͑as measured by secondary ion mass spectrometry͒ decreased the resistivities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…6,10 This effect has also been observed in B 12 P 2 films grown in our group, which may influence the electrical properties of the metal-semiconductor interface independently of any sintering effects. To decouple the effects of annealing-induced changes in the sheet resistance from the sintering of metal contacts, the B 12 P 2 films were annealed in Ar at 800 C for 30 s before any metal contacts were deposited.…”
Section: Experimental Methods and Processingsupporting
confidence: 72%
See 1 more Smart Citation
“…6,10 This effect has also been observed in B 12 P 2 films grown in our group, which may influence the electrical properties of the metal-semiconductor interface independently of any sintering effects. To decouple the effects of annealing-induced changes in the sheet resistance from the sintering of metal contacts, the B 12 P 2 films were annealed in Ar at 800 C for 30 s before any metal contacts were deposited.…”
Section: Experimental Methods and Processingsupporting
confidence: 72%
“…Recent advancements in the improved heteroepitaxial growth of a similar rhombohedral boride, B 12 As 2 , have been achieved on SiC, including suppression of double-position twinning 4,5 and control of p-type doping 6 (note: n-type conductivity in neither B 12 P 2 nor B 12 As 2 has been reported yet). Heterojunction pn-diodes of p-B 12 As 2 /n-SiC have also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs because inter-icosahedral bonding is maintained when an As atom is replaced by a vacancy or either a B, group IV, or group VI atom, and the resulting hole on the As site leads to p-type conductivity. 2 For example, Xu et al 14 demonstrated that the conductivity of high-resistivity p-type IBA epilayers grown on semi-insulating 6H-SiC could be effectively modulated by Si doping, resulting in p-type conduction with a  10 5 reduction in the resistivity. Hall effect measurements on similar as-grown epilayers (%3 lm thick) also exhibited p-type conductivity with hole concentrations 15 in the range (%10 13 -10 16 ) cm À3 .…”
Section: Introductionmentioning
confidence: 99%
“…These atoms have higher electronegativity than that of boron. The resulting materials are B 4 C, B 12 P 2 , B 12 As 2 , and B 12 O 2 (B 4 C has a slightly different structure from the others), which have a wider band gap than α-rh boron according to the electronic structure calculations. Their electrical conduction is also p-type. A discussion of why these materials become p-type was presented by Emin based on the molecular orbital scheme . The hole doping to B 4 C, B 12 P 2 , and B 12 As 2 to achieve superconductivity was proposed by Calandra et al…”
Section: Introductionmentioning
confidence: 99%